Characterization of crosslinked Macrotyloma uniflorum(Horsegram) protein films for packaging and medical applications. (November 2020) - Sakkara, Seema; Venkatesh, Krishna; Reddy, Roopa; Nagananda, G.S.; Meghwal, Murlidhar; Patil, Jagadish H.; Reddy, Narendra
Abstract: Natural polymers such as proteins and polysaccharides are of great demand in packaging and medical applications. Horse gram ( Macrotyloma uniflorum) is a good source of protein and possess excellent antioxidant properties. The present study investigates the development and potential applications of transparent and water-resistant horse gram protein-based films crosslinked with citric acid. Films prepared were further characterized for their physical, chemical and biological properties. Films crosslinked at higher concentrations (15%) of citric acid exhibited 50% reduction in water sorption and reduced water vapor permeability. At 15% citric acid concentration, the films showed excellent free radical scavenging of up to 96%. Also, maximum antimicrobial activity against clinical isolates were observed for the 15% citric acid crosslinked films. Increase in thermal stability and decrease in water vapor permeability was obtained at higher levels of crosslinking. The crosslinked films were cytocompatible and showed potential to be used as substrates for cell culture. Citric acid crosslinked horse gram protein films have good physicochemical properties along with biological activities and could be suitable for applications in the packaging and medical fields. Highlights: Horse gram protein was extracted by alkali method. Transparent and flexible horse gram protein films were developed by simple and inexpensive method. Films were modified by crosslinking with varying concentrations of citric acid. Films developed with 15% citric acid concentration were found to be stable and good antimicrobial property. The crosslinked films were cytocompatible and can be used as a potential substrate for cell culture.